IMMUNOGLOBULIN IGE LEVELS AND CLINICAL DYNAMICS OF ASTHMA IN CHILDREN AND ADOLESCENTS - Abdul Aziz, Danish; Bajwa, Rameen Ata; Muhammad Omar; Viquar , Werdah (Journal of Ayub Medical College Abbottabad, 2024)
Background: The involvement of IgE in type 1 hypersensitivity reactions, including asthma and allergic rhinitis, is widely recognized, and established. However, within this region, there exists a dearth of research exploring the relationship between serum IgE levels and the severity of asthma within the pediatric population. Consequently, the primary objective of this study was to compare the IgE status among children and adolescents diagnosed with asthma, and to examine its association with asthma exacerbations and hospitalizations. By investigating these parameters, we aimed to shed light on the potential role of IgE in influencing disease outcomes in this specific population. Methods: A retrospective study was conducted at The Aga Khan University Hospital from January 2015 to December 2020. Children and adolescents aged 6-18 years who were diagnosed and admitted with asthma, and who had measurement of IgE levels during asthma exacerbation were included in the study. The participants were stratified into two groups based on their IgE levels: normal IgE levels and high IgE levels. Various parameters, including the number of asthma exacerbations, emergency room (ER) visits, hospitalizations, average length of stay, as well as other clinical characteristics such as the presence of allergic rhinitis in the past and a family history of asthma were assessed. Results: A total of 122 patients were included in the study. Of them 57 patients (46.72%) were found to have high IgE levels, and 65 patients (53.28%) had normal IgE levels based on their age group. The average number of exacerbations per year was significantly greater the in high IgE group (3.6±1.09), in comparison to the normal IgE group (2.49±1.22). Conclusion: Higher serum IgE levels correlated with increased asthma exacerbations, emergency room visits, hospitalizations, and a positive family history of asthma, suggesting a potential link between IgE and asthma severity in the pediatric population of Pakistan.